2017
DOI: 10.1016/j.ecoleng.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Retention and survival of E. coli in stormwater biofilters: Role of vegetation, rhizosphere microorganisms and antimicrobial filter media

Abstract: The public health risks associated with pathogens in urban stormwater have been well established, making it necessary to ensure adequate treatment of the stormwater before it is discharged into recreational water bodies or is harvested for reuse.Biofilters, also known as stormwater bioretention systems or raingardens, have shown promising, yet variable, results in reducing indicator bacteria in stormwater. Different biofilter design elements, such as filter media composition and vegetation type, have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…continentale showed some potential antibacterial activity against E. coli and supporting that biofilters can effectively remove fecal microorganisms (Chandrasena et al, 2017). Removal rates of fecal indicator bacteria in stormwater biofilters were assessed based on published literature and laboratory studies, showing that, "66% of the variance in FIB removal rates can be explained by clean bed filtration theory (CBFT, 31%), antecedent dry period (14%), study effect (8%), biofilter age (7%), and the presence or absence of shrubs (6%).…”
Section: Water Qualitymentioning
confidence: 85%
“…continentale showed some potential antibacterial activity against E. coli and supporting that biofilters can effectively remove fecal microorganisms (Chandrasena et al, 2017). Removal rates of fecal indicator bacteria in stormwater biofilters were assessed based on published literature and laboratory studies, showing that, "66% of the variance in FIB removal rates can be explained by clean bed filtration theory (CBFT, 31%), antecedent dry period (14%), study effect (8%), biofilter age (7%), and the presence or absence of shrubs (6%).…”
Section: Water Qualitymentioning
confidence: 85%
“…andChandrasena et al (2017) observed declining FIB removal with time, a trend which was posited to occur due to weakened interaction between FIBs and media surfaces due to biofilm build-up and/or reduced surface sorption capacity(Afrooz and Boehm, 2017) and which was also identified in meta-analysis byParker et al (2017).Vegetation and other biota. Several studies specifically examined vegetation and other biotic communities associated with bioretention systems to better understand their influence on pollutant treatment and other ecosystem services and, in turn, the effect of bioretention design on biotic communities.…”
mentioning
confidence: 90%
“…In the only field-scale study, E. coli removal by fly ash-amended bioretention cells amended exhibited highly variable but generally positive removal efficiencies, but additional testing would be required to determine if observed rates were better than non-amended media (Youngblood et al, 2017). In column studies, the effect of biochar (Afrooz and Boeh, 2017) and Cu 2+ -activated zeolite (Chandrasena et al, 2017) media amendments on FIB were tested. Despite the anti-microbial properties of copper, media augmented with Cu 2+ -exchanged zeolite was not significantly greater than traditional media planted with tea tree or sedge.…”
Section: Field Laboratory and Modeling Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Previous work researching bioretention systems have used local climate data to determine dosing volumes. Chandrasena et al (2017) report using a storm size of 5.75 mm per event while Glaister et al (2017) and Morse et al (2018) used a local yearly average of 540 mm. Each storm event was applied based on 20:1 sizing ratio for each column (TSM 2015).…”
Section: Stormwater Applicationmentioning
confidence: 99%